IN ‘SULTAN’ EPIC ‘HUMAN IS HUMAN’S HELL!’ - Hashimi, Sayed Asghar; Sultani, Farmanullh; Hanifi, Asadullh (American International Journal of Social Science Research, 2021)
Sulatan's poem is an epic of famous poet and author, Abdul Ghafoor Liwal. It has many features of an epic poem and the value of this subject is that the poem was considered to be an epic. The aim of writing this article is to find out what features this epic has in Pashto Language and due to which factors it can be considered to be an epic. Sultan epic has relation with philosophy, psychology, history and culture the same as other epics have. Also, the idea of Habes and Jean – Pal Sartre (Human is human’s hell!), which is taken from Greek Language Play, can be seen in this epic. Finally library research was used to complete the article. Also, clarifying and descriptive methods were used to finish the article. The goal of this article is to state that mostly a human being harms another human being, how we can do well to human beings rather harming them. The value of this research is it makes humans attentive to their deeds and actions in order to avoid doing evil. The finding of this research is that (Sultan) epic poem is an artificial epic and this epic poem states that (Human is human’s hell!) This concept has been taken from Greek Play. Later, Sartor and other scholars have mentioned this concept.